1981
DOI: 10.3133/ofr81682
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic data for urban storm runoff from nine sites in the Denver metropolitan area, Colorado

Abstract: Figure, 1.-Location of monitoring sites and general features. Approach An urban-hydrology monitoring site consists of several types of instrumentation. This instrumentation includes rainfall-measuring equipment, various stage and discharge-meauring devices, water-quality-sampling equipment, atmospheric-deposition sampler, input-output digital recorder, and the system control unit. Rainfall-measuring equipment is of two types-the tipping-bucket rain gage and the 3-inch pipe gage equipped with a float and digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The basin consists of 80 acres, of which 69 acres are offsite and 11 acres are on DFC property (table 2 and Additional basin and channel characteristics such as the area, centroid, channel length, channel slope, basin slope, total relief and elevation of the gaging site are given in table 3 (Alley and Veenhuis, 1979). Several studies of the offsite drainage have been published including one study of potential flood hazard by Grozier and others (1975); three hydro!ogic-data reports by Ellis and Alley (1978), Gibbs (1981), and Gibbs and Doerfer (1982); two hydro!ogic simulation reports by Ell is and Alley (1979) and Ell is and others (1983); and three drainage studies (Hydro-Triad, Ltd., 1973;1974;. The north tributary accounts for an additional 549 acres that drain to a series of retention storage ponds.…”
Section: North Avenue Storm Drainmentioning
confidence: 99%
“…The basin consists of 80 acres, of which 69 acres are offsite and 11 acres are on DFC property (table 2 and Additional basin and channel characteristics such as the area, centroid, channel length, channel slope, basin slope, total relief and elevation of the gaging site are given in table 3 (Alley and Veenhuis, 1979). Several studies of the offsite drainage have been published including one study of potential flood hazard by Grozier and others (1975); three hydro!ogic-data reports by Ellis and Alley (1978), Gibbs (1981), and Gibbs and Doerfer (1982); two hydro!ogic simulation reports by Ell is and Alley (1979) and Ell is and others (1983); and three drainage studies (Hydro-Triad, Ltd., 1973;1974;. The north tributary accounts for an additional 549 acres that drain to a series of retention storage ponds.…”
Section: North Avenue Storm Drainmentioning
confidence: 99%
“…DRCOG concluded that only establishing an urban runoff data base and implementing projects to evaluate the effectiveness of control measures could overcome the poor reliability of model evaluation studies. Hall andDuncan (1980 and1981), in a cooperative study between the Geological Survey and the city of Northglenn, reported that lead, manganese, cadmium, and copper occurred in urban runoff at concentrations exceeding Colorado water-quality standards for agricultural water. The study objectives were to determine the feasibility of using urban runoff for irrigation.…”
Section: Urban Runoff Studies In the Denver Areamentioning
confidence: 99%
“…The location of the rain gages, subcatchments boundaries, and detailed drainage maps are presented by Gibbs (1981) and Gibbs and Doerfer (1982). See figure 2 for the location of monitoring sites.…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 2 more Smart Citations